PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 05 PEKANBARU - Novriani, Delvi; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is the result of social studies class III Pekanbaru SDN 05 is relatively low. The purpose of this study is to improve learning outcomes IPS fourth grade students of SDN 05 Pekanbaru to implement cooperative learning model type STAD. This study took place in SDN 05 Pekanbaru. This research is a classroom action research (PTK). The subjects were students of class III SD Negeri 05 Pekanbaru with a total of 36 students. Based on the results, it can be concluded that the application of cooperative learning model STAD can improve learning outcomes IPS third grade students of SDN 05 Pekanbaru. It is known from IPS learning outcome in each cycle. It is known from the results of students' prior learning with cooperative learning model STAD only be achieved at an average of 68.47. In the first cycle or afterthe implementation of cooperative learning model STAD, the average skills of students increased to 72.36 and then increased to 74.44pada second cycle. Then again increased in the third cycle with a 78.33. Thus, the hypothesis if implemented cooperative learning model STAD, it can improve learning outcomes IPS fourth grade students of SDN 05 Pekanbaru, unacceptable.Keywords : Model STAD cooperative learning , student learning outcomes IPS